Tracer Production Profile Characteristics in Qingcheng Oilfield's Shale Oil Reservoirs with Extra-Long Horizontal Wells - ZHUO Hong; CHENG Bo; WANG Yijun; HE Xiuling; LIU Ping; LI Jie (Cejing jishu)
Tracer monitoring is a new dynamic monitoring technology that is different from conventional cable logging, which can theoretically achieve a direct and accurate quantitative evaluation of the production profile of horizontal wells. This technology effectively solves the problems of cable logging instruments not being able to go down, not being able to measure accurately, not being able to measure completely, and the risk of wellbore accidents in high-angle and long horizontal wells. It improves the level of development of unconventional oil and gas reservoirs. The horizontal well volume fracturing and quasi-natural energy development are used in Chang7 shale oil reservoir of Qingcheng oilfield. Each well has a long horizontal section, many modification clusters, and a high initial oil production. The production patterns between horizontal sections are not clear. The application of fracturing tracer monitoring for shale oil reservoir super-long horizontal well production in China is unprecedented. By studying the tracer production profile test results of the QH9-X well in the Changqing oilfield, based on the differences in the contribution of each section to production, the relationship between the characteristics of production contribution and geological quality, and the relationship between modification methods, we summarized the production patterns of shale oil reservoir horizontal wells. The results show that sand blockage caused the initial outflow from the toe of the well, uneven return caused the water content to decrease slowly, and uneven pressure distribution caused the outflow times of the sections to be uneven. The dominant sweet spot section is the main contributor to oil production. By studying the production profile characteristics of shale oil reservoir super-long horizontal wells in multiple production conditions, it provides realistic basis for fracturing and production of unconventional oil and gas reservoirs' super-long horizontal wells.